(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2011)
Classification of the aquatic plant vegetation of the river Ingul is given using the Braun- Blanquet method. We observed four vegetation classes: Lemnetea, Potametea, Bolboschoenetea maritimi and Phragmito-Magno-Caricetea containing 47 associations, 12 unions and 6 orders. The diversities of plant species in Bolboschoenetea maritimi and Phragmito-Magno-Caricetea are higher than in Lemnetea and Potametea.